Synergistic Activity of Equol and Meropenem against Carbapenem-Resistant Escherichia coli - Hye-Rim Kim; Yong-Bin Eom (MDPI AG, 2021)
The emergence of carbapenem-resistant Enterobacterales (CRE) seriously limits treatment options for bacterial infections. Combined drugs are an effective strategy to treat these resistant strains. This study aimed to evaluate the synergistic effect of equol and meropenem against carbapenem-resistant Escherichia coli. First, this study investigated the antibacterial activity of carbapenems on clinically isolated E. coli strains by analyzing the minimum inhibitory concentrations (MICs). The E. coli strains were all resistant to carbapenem antibiotics. Therefore, we confirmed the cause of carbapenem resistance by detecting blaKPC and blaOXA-48 among the carbapenemase genes using polymerase chain reaction (PCR) analysis. Checkerboard and time-kill analyses confirmed that equol restored the susceptibility of carbapenem-resistant E. coli to meropenem. Also, the transcription levels of specific carbapenemase genes in E. coli were significantly suppressed by equol. The study also evaluated the anti-virulence effects of equol on bacterial biofilm and motility through phenotypic and genotypic analyses. In conclusion, our results revealed that equol had a synergistic effect with meropenem on carbapenem-resistant E. coli. Therefore, this study suggests that equol is a promising antibiotic adjuvant that prevents the expression of carbapenemases and virulence factors in carbapenem-resistant E. coli.